George and the unbreakable code - Hawking, Lucy; Hawking, Stephen Parsons, Garry (Corgi Books London, 2015)
George and his best friend Annie are missing the excitement of their space adventures. But not for long ... Banks start handing out free money; supermarkets can't charge for their food; and aircraft are refusing to fly. It looks like the world's biggest and best computers have all been hacked. George and Annie must travel further into space than ever before in order to find out what - or who - is behind it